Trumbo [videorecording (DVD)] - Cranston, Bryan, 1956-; C. K., Louis; Lane, Diane; Cook, Bruce, 1932-2003 (Universal Studios Home Entertainment, 2016)
The successful career of 1940s screenwriter Dalton Trumbo comes to a crushing end when he and other Hollywood figures are blacklisted for their political beliefs. It tells the story of his fight against the U.S. government and studio bosses in a war over words and freedom, which entangled everyone in Hollywood from Hedda Hopper and John Wayne to Kirk Douglas and Otto Preminger.